A white light luminescent composite nanomaterial and its preparation method and application
By mixing carbon quantum dots, long afterglow nanoparticles and europium doped gadolinium tungstate nanoparticles in a specific proportion, white light luminescence composite nanomaterials with high luminescence efficiency and color stability are prepared, and the existing poor spectral stability of white LEDs is solved. and the problem of high preparation cost.
Patent Information
- Application Number
- CN202411686967.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing white LEDs have poor spectral stability and are difficult to meet the requirements of high-quality lighting. At the same time, the preparation method is complex and the cost is high.
A white light luminescence composite nanomaterial is provided, including carbon quantum dots, long afterglow nanoparticles and europium doped gadolinium tungstate nanoparticles, which are prepared by a simple mixing process to form a white light luminescence material with high luminescence efficiency and thermal stability.
It realizes high color stability and low cost preparation of white light luminescent materials, and the luminescent intensity is less affected by temperature, making it suitable for long-term lighting.
Smart Images

Figure CN119193156B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of white light luminescent materials, and in particular to a white light luminescent composite nano material and a preparation method and application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] At present, white light emitting diodes (LEDs) have multiple advantages such as high energy efficiency, long life, low heat, durability, and environmental protection. They are highly safe and widely used in daily life. Due to their high safety and energy saving, they are not only used for indoor lighting and automotive lighting, but also for display screens. At present, the most common way for white light LEDs to emit light is to use blue light emitting diodes based on gallium nitride (GaN). The light emitted by the blue LED is converted through a phosphor coating (such as YAG phosphor). The phosphor absorbs part of the blue light and re-emit yellow light. The blue light and yellow light are mixed to form white light, which is widely used in the market. However, this process lacks sufficient supplementation of red and green light components, resulting in reduced spectral stability and difficulty in meeting the requirements of high-quality lighting. Another common way is to achieve white light emission by stimulating red, green, and blue luminescent materials, but this technology is relatively complex and has a high production cost. In addition, some white light LED products have the problem of high color temperature, and during use, due to the change of phosphor performance over time and temperature, it may lead to insufficient color stability, color temperature shift or color distortion.
[0004] Therefore, how to provide a white light luminescent material with high color stability, simple preparation method and low cost is an urgent problem to be solved. Summary of the invention
[0005] In view of this, the present invention provides a white light luminescent composite nanomaterial and a preparation method and application thereof. The white light luminescent composite nanomaterial provided by the present invention has the advantages of high luminescence efficiency and good thermal stability, and the preparation process is relatively simple and the cost is low.
[0006] In a first aspect, the present invention provides a white light luminescent composite nanomaterial, comprising carbon quantum dots, long afterglow nanoparticles and europium-doped gadolinium tungstate nanoparticles;
[0007] The molecular formula of the long afterglow nanoparticles is Zn2GeO4:Mn 2+ , where Zn 2+ With Mn 2+The molar ratio is (95-99.5): (0.5-5); the molecular formula of the europium-doped gadolinium tungstate nanoparticles is Gd2(WO4)3:Eu 3+ , where Gd 3+ With Eu 3+ The molar ratio of is 4: (0.8~1.2), and the mass ratio of carbon quantum dots, europium-doped gadolinium tungstate nanoparticles and long afterglow nanoparticles is (0.9~1.1): (0.9~1.1): (0.09~0.11).
[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned white light luminescent composite nanomaterial, comprising the following steps:
[0009] A europium source, a gadolinium source and a tungsten source are mixed and reacted in a solvent in proportion, and a solid product obtained by the reaction is dried and then calcined to obtain europium-doped gadolinium tungstate nanoparticles;
[0010] The carbon quantum dots, europium-doped gadolinium tungstate nanoparticles and long afterglow nanoparticles are mixed in proportion to obtain white light luminescent composite nanomaterials.
[0011] In a third aspect, the present invention provides an application of the above-mentioned white light luminescent composite nanomaterial, wherein the application is to use the white light luminescent composite nanomaterial to prepare a white light LED.
[0012] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0013] (1) The white light luminescent composite nanomaterial provided by the present invention emits white light at an excitation wavelength of 254 nm, and the white light luminescence effect is obvious; moreover, the luminescence intensity of the white light luminescent composite nanomaterial of the present invention is less affected by temperature, and the luminescence stability is good, which is conducive to long-term lighting.
[0014] (2) The preparation process of the white light luminescent composite nanomaterial provided by the present invention is simple and low-cost, which is conducive to industrial large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0016] Figure 1 is a transmission electron microscope image of the carbon quantum dots of Example 1 of the present invention;
[0017] Figure 2 is an emission spectrum of carbon quantum dots according to Example 1 of the present invention;
[0018] Figure 3 is the CIE diagram of the carbon quantum dots of Example 1 of the present invention;
[0019] Figure 4 It is Gd2(WO4)3:Eu prepared in Example 2 of the present invention 3+ SEM images of nanoparticles;
[0020] Figure 5 It is Gd2(WO4)3:Eu prepared in Example 2 of the present invention 3+ X-ray diffraction pattern of nanoparticles;
[0021] Figure 6 It is Gd2(WO4)3:Eu prepared in Example 2 of the present invention 3+ Emission spectra of nanoparticles;
[0022] Figure 7 It is Gd2(WO4)3:Eu prepared in Example 2 of the present invention 3+ CIE diagram of nanoparticles;
[0023] Figure 8 The Zn2GeO4:Mn prepared in Example 3 of the present invention 2+ SEM images of nanoparticles;
[0024] Fig. 9 It is -Zn2GeO4:Mn prepared in Example 3 of the present invention 2+ Emission spectra of nanoparticles;
[0025] Fig.10 The Zn2GeO4:Mn prepared in Example 3 of the present invention 2+ X-ray diffraction pattern of nanoparticles;
[0026] Fig.11 The Zn2GeO4:Mn prepared in Example 3 of the present invention 2+ CIE diagram of nanoparticles;
[0027] Fig.12 is the CIE diagram of the white light luminescent composite nanomaterial prepared in Example 4 of the present invention;
[0028] Fig.13 This is a graph showing the intensity changes of red fluorescence, green fluorescence, and blue fluorescence of the white light luminescent composite nanomaterial prepared in Example 4 of the present invention at 30-300° C., wherein the emission wavelength of red fluorescence is 616.4 nm, the emission wavelength of green fluorescence is 537 nm, and the emission wavelength of blue fluorescence is 395.2 nm;
[0029] Fig.14This is a CIE comparison chart of the white light luminescent composite nanomaterial prepared in Example 4 of the present invention at 30° C. and 300° C. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0031] As described in the background technology, the current white light luminescent materials have the problems of high color temperature and poor color stability. Therefore, the present invention provides a white light luminescent composite nanomaterial, including carbon quantum dots, long afterglow nanoparticles and europium-doped gadolinium tungstate nanoparticles;
[0032] The molecular formula of the long afterglow nanoparticles is Zn2GeO4:Mn 2+ , where Zn 2+ With Mn 2+ The molar ratio is (95-99.5): (0.5-5); the molecular formula of the europium-doped gadolinium tungstate nanoparticles is Gd2(WO4)3:Eu 3+ , where Gd 3+ With Eu 3+ The molar ratio of is 4: (0.8~1.2), and the mass ratio of carbon quantum dots, europium-doped gadolinium tungstate nanoparticles and long afterglow nanoparticles is (0.9~1.1): (0.9~1.1): (0.09~0.11).
[0033] In the above-mentioned white light luminescent composite nanomaterials of the present invention, carbon quantum dots, long afterglow nanoparticles, and europium-doped gadolinium tungstate nanoparticles all have high stability, high luminescence intensity, and are simple to prepare; when the three are mixed in a specific proportion, a white light luminescent composite nanomaterial with high luminescence intensity and good color stability can be obtained, and even at a high temperature of 300°C, the color deviation is still very small.
[0034] In the present invention, the Zn in the long afterglow nanoparticles 2+ With Mn 2+ The molar ratio of Gd in the europium-doped gadolinium tungstate nanoparticles is preferably 99:1. 3+ With Eu 3+ The molar ratio of is preferably 4:1, and the mass ratio of carbon quantum dots, gadolinium tungstate nanoparticles and long afterglow nanoparticles is preferably 1:1:0.1. Under the above ratio, the chromaticity diagram (CIE) coordinate position of the finally obtained white light luminescent composite nanomaterial is (0.3214, 0.3258), which is near white light.
[0035] The present invention also provides a method for preparing the above-mentioned white light luminescent composite nanomaterial, comprising the following steps:
[0036] A europium source, a gadolinium source and a tungsten source are mixed and reacted in a solvent in proportion, and a solid product obtained by the reaction is dried and then calcined to obtain europium-doped gadolinium tungstate nanoparticles;
[0037] The carbon quantum dots, europium-doped gadolinium tungstate nanoparticles and long afterglow nanoparticles are mixed in proportion to obtain white light luminescent composite nanomaterials.
[0038] In the present invention, the step of mixing and reacting the europium source, the gadolinium source and the tungsten source in a solvent in proportion is specifically as follows: dissolving the europium source and the gadolinium source in a solvent to form a mixed solution, dissolving the tungsten source in a solvent to form a tungsten source solution, and then adding the mixed solution to the tungsten source solution to react. After the reaction is completed, a gadolinium tungstate precursor is obtained.
[0039] In the present invention, the europium source is selected from europium chloride; the gadolinium source is selected from gadolinium chloride; and the tungsten source is selected from sodium tungstate.
[0040] In the present invention, the solvent is water, and the amount of the solvent used is not particularly limited, and the amount of the solvent commonly used in the art can be used. The reaction temperature is 50-80°C, more preferably 55-70°C; the reaction time is 0.5-3h; more preferably 0.8-1.5h.
[0041] The reaction system of the present invention in which the europium source, the gadolinium source and the tungsten source are mixed in a solvent in proportion and reacted further comprises a metal complexing agent, and the metal complexing agent is selected from ethylenediaminetetraacetic acid. The presence of the metal complexing agent can promote the occurrence of the reaction. The addition amount of the metal complexing agent is preferably 2-5wt% of the total mass of the europium source, the gadolinium source and the tungsten source.
[0042] The present invention further comprises the steps of centrifugation and washing to obtain a solid product after the reaction of the europium source, the gadolinium source and the tungsten source is completed. The present invention does not impose any special restrictions on the specific steps of centrifugation and washing, and the methods commonly used by those skilled in the art can be used.
[0043] In the present invention, the calcination temperature is 800-1000°C, more preferably 850-950°C; the calcination time is 3-6h. In the present invention, the calcination is carried out in an air atmosphere, and europium-doped gadolinium tungstate nanoparticles are obtained by calcination, and the europium-doped gadolinium tungstate nanoparticles after calcination have fewer surface defects and high stability.
[0044] In the present invention, the preparation method of the long afterglow nanoparticles comprises the following steps: mixing manganese salt, zinc salt and dilute nitric acid, adding Na2GeO3 aqueous solution, adjusting the pH to 7.2-7.9, performing hydrothermal synthesis reaction, and purifying to obtain the long afterglow nanoparticles.
[0045] The conditions for the hydrothermal synthesis reaction of the long afterglow nanoparticles of the present invention are: temperature of 210-230°C, preferably 220°C, time of 12-24 h, preferably 16 h; the molar ratio of zinc salt to manganese salt is (95-99.5):(0.5-5), preferably 99:1.
[0046] The present invention does not impose any special restrictions on the purification method of the long afterglow nanoparticles, and a common purification method in the art can be used. The purification method of the present invention is to centrifuge, wash and dry the liquid after the hydrothermal synthesis reaction to obtain the long afterglow nanoparticles.
[0047] The present invention does not impose any special restrictions on the preparation method of carbon quantum dots, and the preparation method of carbon quantum dots can be prepared by the hydrothermal method commonly used in the art. The preferred method for preparing carbon quantum dots of the present invention comprises the following steps: adding ethanolamine to an aqueous solution containing citric acid, stirring vigorously until clear, and performing a hydrothermal synthesis reaction at 170-200°C for 5-8 hours to obtain. In the present invention, the molar ratio of ethanolamine to citric acid is 1.8-2.2:1, preferably 2:1. Using ethanolamine and citric acid in the above molar ratio as raw materials, the synthesized carbon quantum dots have good luminescence properties.
[0048] The present invention does not impose any special restrictions on the process of mixing carbon quantum dots, europium-doped gadolinium tungstate nanoparticles and long afterglow nanoparticles in proportion, as long as a white light luminescent composite nanomaterial with uniform composition can be obtained. The present invention preferably adopts grinding mixing.
[0049] The present invention also provides an application of the white light luminescent composite nanomaterial or the white light luminescent composite nanomaterial prepared by the above preparation method, wherein the application is to use the white light luminescent composite nanomaterial to prepare a white light LED. The white light luminescent composite nanomaterial of the present invention can emit white light under 254nm laser excitation, has high luminescence intensity, and has good temperature stability.
[0050] The technical solution of the present invention is further described below in conjunction with specific embodiments. The present invention has no particular limitation on the source of the reagents in the embodiments, and commercially available products known to those skilled in the art can be used.
[0051] Example 1
[0052] This embodiment provides a preparation of carbon quantum dots (CDs), comprising the following steps:
[0053] (1) Weigh 19.212 g of citric acid (0.1 mol) into a beaker, add 20 mL of water and stir to obtain a citric acid aqueous solution. Then, drop 12 mL of ethanolamine (0.2 mol) aqueous solution into the citric acid aqueous solution and stir vigorously until the solution becomes clear.
[0054] (2) The clear solution was sealed in a reactor, heated to 180°C and maintained for 6 h, and then naturally cooled to room temperature to obtain a reddish-brown liquid.
[0055] (3) Rotary evaporation: The reddish brown liquid obtained in step (2) is subjected to rotary evaporation, and then dialyzed with a dialysis bag for 3 days to remove unreacted ethanolamine precursor and small molecule products, and then freeze-dried to obtain carbon quantum dots.
[0056] The transmission electron microscope (TEM) image of the carbon quantum dots (CDs) obtained in this example is measured. Figure 1 As shown in the figure, it can be seen that CDs are spherical and about 3nm in size.
[0057] Determine the emission spectrum of carbon quantum dots, such as Figure 2 As shown, when the wavelength of the excitation light source used is 254nm and the power is 4W, its emission peak is around 395nm.
[0058] Figure 3 This is the chromaticity diagram (CIE diagram) of carbon quantum dots. From the diagram, we can see that its coordinate position is at (0.1531, 0.0496).
[0059] Example 2
[0060] This embodiment provides Gd2(WO4)3:Eu 3+ The preparation of nanoparticles includes the following steps:
[0061] (1) Add 1.0166 g GdCl3 (1.6 mmol), 0.2931 g EuCl3 (0.4 mmol), 0.1 g ethylenediaminetetraacetic acid (EDTA), and 20 mL water to beaker A and stir until the solution becomes clear.
[0062] (2) Add 1.9791 g Na2WO4 and 60 mL water to beaker B and stir until the solution becomes clear.
[0063] (3) The solution in beaker A was dripped into beaker B and stirred at 60°C for 1 h. The reaction solution was then centrifuged at 10,000 r / min for 10 min, washed with water, and dried to obtain a precursor powder.
[0064] (4) Grind the above precursor powder in a mortar, transfer it to a box-type resistance furnace, calcine it at 900℃ for 4h, and then grind it for 1h to obtain Gd2(WO4)3:Eu 3+ Nanoparticles.
[0065] Figure 4 Gd2(WO4)3:Eu prepared in this example 3+Scanning electron microscope image of nanoparticles. It can be seen from the figure that Gd2(WO4)3:Eu 3+ The nanoparticles are rod-shaped.
[0066] Figure 5 Gd2(WO4)3:Eu prepared in this example 3+ X-ray diffraction pattern of nanoparticles, Gd2(WO4)3:Eu 3+ The XRD pattern of the nanoparticles is completely consistent with the standard card (PDF#23-1076), indicating that the prepared Gd2(WO4)3:Eu 3+ The nanoparticles are pure phase and do not have any impurities.
[0067] Figure 6 Gd2(WO4)3:Eu prepared in this example 3+ The emission spectrum of the nanoparticles shows that when the wavelength of the excitation light source used is 254nm and the power is 4W, the main emission peak is around 616nm.
[0068] Figure 7 Gd2(WO4)3:Eu prepared in this example 3+ The CIE diagram of the nanoparticles is at (0.6566, 0.343).
[0069] Example 3
[0070] This embodiment provides a long afterglow nanoparticle Zn2GeO4:Mn 2+ The preparation comprises the following steps:
[0071] (1) Add Zn(NO3)2 (1.98 mmol), MnCl2 (0.02 mmol) into a beaker, then add 300 μL of 1 wt% dilute nitric acid and 20 mL of water, stir to dissolve, and obtain a mixed solution;
[0072] (2) Dissolve 10 mmol of NaOH in 10 mL of aqueous solution until the NaOH is completely dissolved, then add 2 mmol of GeO2 and stir to obtain a Na2GeO3 solution. Use a syringe to take 5.5 mL of the Na2GeO3 solution and add it to the mixed solution of step (1), and stir for 30 minutes.
[0073] (3) The pH of the solution in step (2) was adjusted to 7.6 using 1 wt % NaOH solution, stirred for 30 minutes, and then transferred into a hydrothermal reactor for reaction at 220 ° C for 16 hours.
[0074] (4) The solution after the reaction was centrifuged at 10000 r / min for 10 min to obtain Zn2GeO4: Mn 2+ The nanoparticles were washed with water and dried to obtain Zn2GeO4:Mn2+ Nanoparticles.
[0075] Figure 8 The Zn2GeO4:Mn prepared in this example 2+ SEM images of nanoparticles show that Zn2GeO4:Mn 2+ The nanoparticles are rod-shaped, with an average length of about 100nm and an average width of about 35nm.
[0076] Fig. 9 The Zn2GeO4:Mn prepared in this example 2+ The emission spectrum of the nanoparticles shows that when the wavelength of the excitation light source used is 254nm and the power is 4W, the emission peak is at 537nm.
[0077] Fig.10 The Zn2GeO4:Mn prepared in this example 2+ X-ray diffraction pattern of nanoparticles, Zn2GeO4:Mn 2+ The XRD pattern of the nanoparticles is completely consistent with the standard card (PDF#11-0687), indicating that the prepared Zn2GeO4:Mn 2+ The nanoparticles are pure phase and do not have any impurities.
[0078] Fig.11 The Zn2GeO4:Mn prepared in this example 2+ The CIE diagram of the nanoparticles is at (0.237, 0.6847).
[0079] Example 4
[0080] This embodiment provides a method for preparing a white light luminescent composite nanomaterial, and the specific steps are as follows:
[0081] First, the CDs of Example 1 and the Gd2(WO4)3:Eu of Example 2 were 3+ and Zn2GeO4:Mn of Example 3 2+ The three were mixed and ground in a mass ratio of 1:1:1. The ratio of the three was changed according to the CIE diagram. The grinding was continued until the composite nanomaterial emitted white light at an excitation wavelength of 254nm (excitation power of 4W). 2+ and Gd2(WO4)3:Eu 3+ The mass ratio of the three is 1:1:0.1, thereby obtaining a white luminescent composite nanomaterial.
[0082] Fig.12 The CIE diagram of the white light luminescent composite nanomaterial prepared in this embodiment is provided. It can be seen that the coordinate position is (0.3214, 0.3258), which is near white light.
[0083] 0.5g of white light luminescent composite nanomaterial was placed in a temperature variable device, the position of the temperature variable device was fixed, and then the temperature variable device was heated (30-300℃). Under the irradiation of a laser with an excitation power of 4W and an excitation wavelength of 254nm, the red fluorescence, green fluorescence, and blue fluorescence emission spectra of the white light luminescent composite nanomaterial were tested using a spectrometer. Among them, the emission wavelength of red fluorescence was 616.4nm, corresponding to the europium-doped gadolinium tungstate nanoparticles (Gd2(WO4)3:Eu 3+ ); The emission wavelength of green fluorescence is 537nm, corresponding to the long afterglow nanoparticles (Zn2GeO4:Mn 2+ The emission wavelength of blue fluorescence is 395.2nm, corresponding to carbon quantum dots (CDs); the fluorescence intensity of red, green and blue fluorescence at 254nm changes with temperature, as shown in Fig.13 As shown, it can be seen that the fluorescence intensity fluctuates very little with the increase of temperature and remains basically stable, indicating that the prepared white light luminescent composite nanomaterial has good temperature stability.
[0084] Fig.14 This is the CIE comparison diagram of the white light luminescent composite nanomaterial prepared in this embodiment at 30°C and 300°C. It can be seen that at 300°C, the coordinate position is (0.3272, 0.3531), which has a small deviation from the coordinate position (0.3214, 0.3258) at 30°C, indicating that this white light luminescent composite nanomaterial has good color stability and is less affected by temperature.
[0085] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A white light emitting composite nanomaterial, characterized in that: These include carbon quantum dots, long-lasting nanoparticles, and europium-doped gadolinium tungstate nanoparticles; The molecular formula of the long afterglow nanoparticles is Zn2GeO4:Mn 2+ , where Zn 2+ With Mn 2+ The molar ratio is (95-99.5): (0.5-5); the molecular formula of the europium-doped gadolinium tungstate nanoparticles is Gd2(WO4)3:Eu 3+ , where Gd 3+ With Eu 3+ The molar ratio of is 4: (0.8~1.2), and the mass ratio of carbon quantum dots, europium-doped gadolinium tungstate nanoparticles and long afterglow nanoparticles is (0.9~1.1): (0.9~1.1): (0.09~0.11).
2. The white light emitting composite nanomaterial according to claim 1, characterized in that: The long afterglow nanoparticles contain Zn 2 + With Mn 2+ The molar ratio of Gd in the europium-doped gadolinium tungstate nanoparticles is 99:
1. 3+ With Eu 3+ The molar ratio of is 4:1, and the mass ratio of carbon quantum dots, gadolinium tungstate nanoparticles and long afterglow nanoparticles is 1:1:0.
1.
3. The method for preparing a white light luminescent composite nanomaterial according to any one of claims 1 to 2, characterized in that: The steps include: A europium source, a gadolinium source and a tungsten source are mixed and reacted in a solvent in proportion, and a solid product obtained by the reaction is dried and then calcined to obtain europium-doped gadolinium tungstate nanoparticles; The carbon quantum dots, europium-doped gadolinium tungstate nanoparticles and long afterglow nanoparticles are mixed in proportion to obtain a white light luminescent composite nanomaterial.
4. The preparation method according to claim 3, characterized in that: The europium source is selected from europium chloride; the gadolinium source is selected from gadolinium chloride; and the tungsten source is selected from sodium tungstate.
5. The preparation method according to claim 3, characterized in that: The solvent is water, the reaction temperature is 50-80° C., and the reaction time is 0.5-3 h.
6. The preparation method according to claim 3, characterized in that: The reaction system also includes a metal complexing agent, and the metal complexing agent is selected from ethylenediaminetetraacetic acid.
7. The preparation method according to claim 3, characterized in that: The calcination temperature is 800-1000° C., and the calcination time is 3-6 hours.
8. The preparation method according to claim 3, characterized in that: The preparation method of the long afterglow nanoparticles comprises the following steps: mixing manganese salt, zinc salt and dilute nitric acid, adding Na2GeO3 aqueous solution, adjusting the pH to 7.2-7.9, performing a hydrothermal synthesis reaction, and purifying to obtain the long afterglow nanoparticles.
9. The preparation method according to claim 3, characterized in that: The preparation method of the carbon quantum dots comprises the following steps: adding ethanolamine to an aqueous solution containing citric acid, stirring until clear, performing a hydrothermal synthesis reaction at 170-200° C. for 5-8 hours, and purifying the solution.
10. Use of the white light luminescent composite nanomaterial according to claim 1 or 2 or the white light luminescent composite nanomaterial prepared by the preparation method according to any one of claims 3 to 9, characterized in that: The application is to use the white light luminescent composite nanomaterial to prepare white light LEDs.
Citation Information
Patent Citations
Near-full-spectrum fluorescent nanocarbon dots and preparation method thereof
CN105647526A
Europium-doped gadolinium tungstate fluorescent powder preparation method
CN108531178A